Synthesis and characterization of stiff, self-crosslinked thermoresponsive DMAA hydrogels - Carlos Rueda, Juan; Santillan, Fatima; Komber, Hartmut; Voit, Brigitte (Polymers, 2020)
Stiff thermosensitive hydrogels (HG) were synthesized by self-crosslinking free radical polymerization of N, N-dimethylacrylamide (DMAA) and N-isopropylacrylamide (NIPAAm), adjusting the degree of swelling by carboxylate-containing sodium acrylate (NaAc) or a 2-oxazoline macromonomer (MM). The formation of hydrogels was possible due to the self-crosslinking property of DMAA when polymerized with peroxodisulfate initiator type. The MM was synthetized by the ring-opening cationic polymerization of 2-methyl-2-oxazoline (MeOxa) and methyl-3-(oxazol-2-yl)-propionate (EsterOxa), and contained a polymerizable styryl endgroup. After ester hydrolysis of EsterOxa units, a carboxylate-containing MM was obtained. The structure of the hydrogels was confirmed by 1Hhigh-resolution (HR)-MASNMRspectroscopy. Suitable conditions and compositions of the comonomers have been found, which allowed efficient self-crosslinking as well as a thermoresponsive swelling in water. Incorporation of both the polar comonomer and the macromonomer, in small amounts furthermore allowed the adjustment of the degree of swelling. However, the macromonomer was better suited to retain the thermoresponsive behavior of the poly (NIPAAm) due to a phase separation of the tangling polyoxazoline side chains. Thermogravimetric analysis determined that the hydrogels were stable up to 350 ffiC, and dynamic mechanical analysis characterized a viscoelastic behavior of the hydrogels, properties that are required, for example, for possible use as an actuator material.
CRIS-Team Scopus Importer:2022-04-14
Keywords: DMAA hydrogel; Macromondomer; Polyoxazoline; Self-crosslinking; Thermosensitivity